Topical steroid application can induce branched/reticular vessels in Bowen disease on the upper trunk - Hiroyo Hashimoto; Yaei Togawa; Naoki Aoyagi; Ryoji Kurita; Rena Oguma; Mari Iwasawa; Keisuke Suehiro; Hiroyuki Matsue (PAGEPress Publications, 2020)
We aimed to elucidate the dermoscopic vasculature of patients with Bowen Disease (BD) that was misdiagnosed as chronic eczema and had branched and/or reticular vessels after topical steroid application. The medical records of 19 patients with BD on the upper trunk were retrospectively reviewed for steroid use history, vascular structure observed in dermoscopy, and corresponding histological findings. Four patients treated with strong topical steroids showed remarkable branched and/or reticular vessels on dermoscopy. Histopathology showed partial epidermal atrophy with irregular thin elongation of the rete ridges, atypical keratinocyte proliferation in the epidermis, and vasodilation in the superficial dermis. We considered that vasodilation and partial epidermal atrophy may be induced by topical steroid application in BD-affected areas. In cases of suspected BD with reddish-brown plaque showing branched and/or reticulated vessels in dermoscopy, confirming a history of topical steroid use is helpful.